Effect of NωNLA or dexamethasone on vascular hyporeactivity induced by E. coli endotoxin in sham and adrenalectomized rats - Ambrosio, Ana Elisa [UNESP]; Fracasso, José Francisco [UNESP] (My University, 2000)
Induction of iNOS by bacterial products is considered to be part of the defense mechanism against infection. However, it has been suggested that the bacterial-induced NO-overproduction may be involved in the vascular hyporeactivity and in septic shock. It is well known that glucocorticoids prevent the induction of iNOS by Etx in rats. In the present study, dexamethasone diminished but not abolished Etx-induced vascular hyporeactivity in rats. Our results showed that the inhibition of iNOS protects sham rats against the lethal shock produced by Etx, but, in Adx rats, the NωNLA, an iNOS inhibitor, did not reduce Etx-induced mortality. Interestingly, the lack of glucocorticoid impaired the protective effect of NωNLA against Etx-induced hyporeactivity and shock in rats. A conceivable pharmacological approach to protect tissues against deleterious effect of excessive NO production includes inhibition of the iNOS, because the absence of glucocorticoid may increase the iNOS gene expression, with NO-overproduction induced by Etx, suggesting that the glucocorticoids might be of therapeutic value for the treatment of hyporeactivity and shock triggered by sepsis.
Keywords: Dexamethasone; Endotoxin; NωNLA; Nitric oxide; NO-synthesis; Vascular hyporeactivity; dexamethasone; Escherichia coli endotoxin; glucocorticoid; n(g) nitroarginine; nitric oxide; nitric oxide synthase; nitric oxide synthase inhibitor; adrenalectomy; animal experiment; animal model; blood vessel reactivity; controlled study; defense mechanism; drug effect; enzyme induction; enzyme inhibition; gene expression; male; mortality; nonhuman; rat; septic shock